α2-Macroglobulin Is a Significant In Vivo Inhibitor of Activated Protein C and Low APC:α2M Levels Are Associated with Venous Thromboembolism - Martos, Laura; Ramón, Luis Andrés; Oto, Julia; Fernández-Pardo, Álvaro; Bonanad, Santiago; Cid, Ana Rosa; Gruber, Andras; Griffin, John H.; España, Francisco; Navarro, Silvia; Medina, Pilar (Thrombosis and Haemostasis, 2018)
Background Activated protein C (APC) is a major regulator of thrombin formation. Two major plasma inhibitors form complexes with APC, protein C inhibitor (PCI) and α1-antitrypsin (α1AT), and these complexes have been quantified by specific enzyme-linked immunosorbent assays (ELISAs). Also, complexes of APC with α2-macroglobulin (α2M) have been observed by immunoblotting. Here, we report an ELISA for APC:α2M complexes in plasma.Methods Plasma samples were pre-treated with dithiothreitol and then with iodoacetamide. The detection range of the newly developed APC:α2M assay was 0.031 to 8.0 ng/mL of complexed APC. Following infusions of APC in humans and baboons, complexes of APC with α2M, PCI and α1AT were quantified. These complexes as well as circulating APC were also measured in 121 patients with a history of venous thromboembolism (VTE) and 119 matched controls.Results In all the in vivo experiments, α2M was a significant APC inhibitor. The VTE case–control study showed that VTE patients had significantly lower APC:α2M and APC levels than the controls (p < 0.001). Individuals in the lowest quartile of APC:α2M or the lowest quartile of APC had approximately four times more VTE risk than those in the highest quartile of APC:α2M or of APC. The risk increased for individuals with low levels of both parameters.Conclusion The APC:α2M assay reported here may be useful to help monitor the in vivo fate of APC in plasma. In addition, our results show that a low APC:α2M level is associated with increased VTE risk.
Keywords: activated protein C; α2-macroglobulin; ELISA; baboon; complexes